The role of MIF, cyclinD1 and ERK in the development of pulmonary hypertension in broilers. Issue 2 (4th March 2017) - Li, Haoyun; Wang, Yanmei; Chen, Lingli; Han, Lijuan; Li, Lifang; He, Han; Li, Yuan; Huang, Nan; Ren, Hao; Pei, Fangying; Li, Guilan; Cheng, Jia; et al.
ABSTRACT: Pulmonary hypertension (PH) is a major disease in the broiler breeding industry. During PH, the pulmonary artery undergoes remodelling, which is caused by pulmonary vascular smooth muscle cell proliferation. CyclinD1 regulates cell proliferation. This study investigated the role of cyclinD1 in the development of PH in broilers, and which bioactivators and signalling pathway are involved in the pathological process. The PH group contained 3–4-week-old broilers with clinical PH, and the healthy group broilers from the same flock without PH. Histopathology indicated pulmonary arterial walls were thicker in the PH group compared with the healthy group. Target gene expressions of macrophage migration inhibitory factor (MIF), extracellular signal-regulated kinase (ERK), and cyclinD1 detected by quantitative real-time PCR were upregulated in the PH group compared with the healthy group. Immunohistochemistry showed MIF, phosphorylated ERK (p-ERK) and cyclinD1 were present on pulmonary vascular walls; MIF was present in the cytoplasm of arterial endothelial cells and smooth muscle cells; p-ERK and cyclinD1 were present in smooth muscle cell cytoplasm. Western blotting demonstrated that MIF, p-ERKand cyclinD1 levels were significantly higher ( P  < 0.01) in the PH group compared with the healthy group. In summary, increased MIF in PH broiler pulmonary arteries upregulated cyclinD1 via the ERK signalling pathway to induce pulmonary vascular smooth muscle cell proliferation, causing pulmonary artery remodelling and hypertension.